FIGURE OF SPEECH IN THE ELECTION DEBATE BETWEEN DONALD TRUMP AND JOE BIDEN - Dedi Bangun; Syahron Lubis; Ridwan Hanafiah (Universitas Islam Sumatera Utara, 2022)
This research is aimed at identifying the types and functions of figures of speech in The New York Times selected headlines under the issue of Donald Trump and Joe Biden 1st Presidential Debating 2020. The study of Stylistic is employed since this research investigates language and style which can be seen in figurative language through figures of speech in the objects of study. This research is done by descriptive qualitative method. The data of this research are taken from The New York Times official website. The data are the sentences referring to figures of speech. Inductive analysis method is used in the analysis of the data, then triangulation is used to establish the reliability of the data, so that it can enhance trustworthiness. The research results show six of twelve types of figures of speech are found based on Perrine’s theory, i.e. metaphor, simile, personification, symbol, paradox and overstatement/hyperbole. Each type of figure of speech has its particular function or functions. However, there are only two of four functions of figures of speech found based on Perrine’s theory, i.e. to add emotional intensity and to say much in a brief compass. Metaphor, simile, and overstatement/hyperbole carry both functions, adding emotional intensity to the readers and saying much in a brief compass.